Trans-acting non-synonymous variant of FOXA1 predisposes to hepatocellular carcinoma through modulating FOXA1-ERα transcriptional program and may have undergone natural selection. (11th August 2019) - Wang, Sheng; Xiang, Chan; Mou, Lin; Yang, Yuan; Zhong, Rong; Wang, Liyan; Sun, Chang; Qin, Zhaoyu; Yang, Jingmin; Qian, Ji; Zhao, Yuanyuan; Wang, Yi; et al.
Abstract: Interplay of pioneer transcription factor forkhead box A1 (FOXA1) and estrogen receptor has been implicated in sexual dimorphism in hepatocellular carcinoma (HCC), but etiological relevance of its polymorphism was unknown. In the case control study (1152 patients versus1242 controls), we observed significant increase in HCC susceptibility in hepatitis B virus carriers associated with a non-synonymous Thr83Ala variant of FOXA1 (odds ratio [OR], 1.28; 95% confidence interval [CI], 1.11−1.48, for Ala83-containing genotype, after validation in an independent population with 933 patients versus 1030 controls), a tightly linked (CGC)5/6or7 repeat polymorphism at its promoter (OR 1.32; 95% CI 1.10–1.60, for (CGC)6or7 -repeat-containing genotype), and their combined haplotype (OR 1.50; 95% CI 1.24–1.81, for (CGC)6or7 −Ala83 haplotype). The susceptible FOXA1-Ala83 impairs its interaction with ERα, attenuates transactivation toward some of their dual target genes, such as type 1 iodothyronine deiodinase, UDP glucuronosyltransferase 2 family, polypeptide B17 and sodium/taurocholate cotransporting polypeptide, but correlates with strengthened cellular expression of α-fetoprotein ( AFP ) and elevated AFP serum concentration in HCC patients ( n = 1096). The susceptible FOXA1 cis -variant with (CGC)6or7 repeat strengthens the binding to transcription factor early growth response 1 and enhances promoter activity and gene expression. Evolutionary population genetics analyses with public datasets reveal significant population differentiation and unique haplotype structure of the derived protective FOXA1-Thr83 and suggest that it may have undergone positive natural selection in Chinese population. These findings epidemiologically highlight the functional significance of FOXA1-ERα transcriptional program and regulatory network in liver cancer development. Abstract : Interplay of pioneer factor FOXA1 and estrogen receptors is implicated in liver cancer. Our study suggests that FOXA1 non-synonymous variant impaired its interaction with ERα, attenuates transactivation toward their cognate target genes, is genetically associated with liver cancer susceptibility, and may have undergone natural selection.